2013
DOI: 10.1007/s00213-013-3099-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intranasal oxytocin treatment on conditioned fear extinction and recall in a healthy human sample

Abstract: Rationale To improve outcomes for patients undergoing extinction-based therapies (e.g. exposure therapy) for anxiety disorders such as post-traumatic stress disorder, there has been interest in identifying pharmaceutical compounds which might facilitate fear extinction learning and recall. Oxytocin (OT) is a mammalian neuropeptide that modulates activation of fear extinction-based neural circuits and fear responses. Little is known however about the effects of OT treatment on conditioned fear responding and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 45 publications
(66 reference statements)
10
98
1
1
Order By: Relevance
“…To test the effects of oxytocin on extinction, we employed a common 2-day protocol; on the first day, fear conditioning was followed by drug treatment and subsequent extinction training trials, with the fear recall test 24 h later. We found a significant increase in extinction recall in the oxytocin group (i.e., less fear than placebo), suggesting a potential enhancement of extinction encoding/ consolidation (Acheson et al 2013). A recent study using fMRI with a very similar 1-day design of fear conditioning being followed by treatment and extinction training confirmed that within-session extinction could be enhanced by pretraining oxytocin (Eckstein et al 2014).…”
Section: Practical Considerations When Using Learned Fear Processes Asupporting
confidence: 59%
See 2 more Smart Citations
“…To test the effects of oxytocin on extinction, we employed a common 2-day protocol; on the first day, fear conditioning was followed by drug treatment and subsequent extinction training trials, with the fear recall test 24 h later. We found a significant increase in extinction recall in the oxytocin group (i.e., less fear than placebo), suggesting a potential enhancement of extinction encoding/ consolidation (Acheson et al 2013). A recent study using fMRI with a very similar 1-day design of fear conditioning being followed by treatment and extinction training confirmed that within-session extinction could be enhanced by pretraining oxytocin (Eckstein et al 2014).…”
Section: Practical Considerations When Using Learned Fear Processes Asupporting
confidence: 59%
“…It has been suggested that this lack of translation of DCS effects on extinction in animals to extinction in healthy human subjects may be because extinction protocols in the laboratory are not probing "automatic" learned fear and extinction processes, but are instead governed by top-down executive functions (Grillon 2009). More recent studies, however, suggest that extinction in healthy controls is sensitive to putative extinction enhancing drugs such as cannabinoid receptor agonists and oxytocin (Acheson et al 2013;Das et al 2013;Eckstein et al 2014;Rabinak et al 2013), which suggests that these tests are "translational" in that they are sensitive to drugs that have shown efficacy in animal extinction studies (Singewald et al 2015). Whether these drugs can then also make the leap to enhancement of exposure therapy or PTSD treatment is thus far mixed.…”
Section: Pharmacological Approaches For Fear Extinction In Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…OT has anxiolytic properties both at the neurobiological and behavioral level. Behaviorally, OT administration resulted in decreased subjective anxiety during a public speaking stressor in healthy individuals (de Oliveira et al, 2012) and increased (recall of) extinction learning in both rodents (Zoicas et al, 2014) and healthy males (Acheson et al, 2013). In addition, functional MRI (fMRI) studies have shown that OT administration dampened amygdala reactivity toward emotional stimuli in healthy males (Kirsch et al, 2005), males with generalized social anxiety disorder (GSAD; Labuschagne et al, 2010) and females with borderline personality disorder (BPD; Bertsch et al, 2013), although findings for females have been mixed (Domes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…fMRI studies in humans showed that a single administration of OT attenuated amygdala reactivity to negative emotional stimuli and enhanced amygdala-medial PFC resting-state FC in healthy males (Kirsch et al, 2005;Sripada et al, 2012a), and males with generalized social anxiety disorder (Dodhia et al, 2014;Labuschagne et al, 2010). Moreover, OT attenuated amygdala reactivity and increased PFC reactivity during fear extinction (Eckstein et al, 2015), and increased fear extinction recall after fear extinction training (Acheson et al, 2013) in healthy males. Similarly, OT dampened amygdala and dACC reactivity to fear-conditioned faces, while reducing negative ratings of these faces (Petrovic et al, 2008).…”
Section: Introductionmentioning
confidence: 99%